A importância da experimentação nas aulas de ciências no ensino fundamental maior no município de Cametá - BAIA, Maria de Nazaré da Rocha (2024)
Science teaching currently assumes an increasingly relevant role for society, so it is up to schools to carry out necessary reformulations in pedagogical practice in such a way that the student's attention turns to Science, arousing their interest and curiosity. The present work titled as: The importance of experimentation in Science classes in Higher Elementary School in the Municipality of Cametá presents a methodology that unites theory with practice, thus corroborating with knowledge assimilation. The methodological-theoretical process took place in two ways: a priori, a bibliographic survey was carried out; using some references of authors such as: CARL ROGERS (1972), PAULO FREIRE (1997), VYGOTSKY (2010), FUMAGALLI (1988), CHASSOT (2011), GIORDAN (1999), PCNS (1997), and then the field research, with an intervention and application of the questionnaire in a 6th grade class in order to analyze what students think about the use of this methodology in science classes. Through the analyzes carried out, it was possible to understand that the use of practical experiments contributes significantly to the process of teaching and learning Science, as this tool facilitates the understanding of concepts taught in class. The objective is based on demonstrating how the experiments help in the teaching process. Through this study, it was possible to attest that the experiments can collaborate so that students have more autonomy and criticality. This research presents a contribution that are the experiments, being this one more resource to be used in the classroom by the teachers, since it makes the class more interactive and dynamic.